The role of Tunisian civil society in functional public policy governance:: Tunisian General Labour Union as a model - Kime, Samir; Kouachi , Ouahiba (Journal of Human Sciences, 2020)
This paper aims to analyze the role of civil society organizations in public policy governance by reading the role of the Tunisian General Labour Union in operational public policy making in Tunisia. The study result that the Tunisian General Labour Union has some structural and functional characters let it to play an important role as an actor in public policy making. Also by its social debate policy let it gain much positive influence to the operational public policy.